Solid non-enhancing cerebellar pilocytic astrocytoma case report. (February 2019) - Towner, James E.; Azriel, Amit; Rogers, TeWhiti; Box, Georgia; Adamides, Alexios A.; Drummond, Kate
Highlights: Pilocytic astrocytoma (PA) is a low-grade glial tumor. Classic radiologic finding is a cerebellar cystic mass with enhancing solid nodule. Uncommon radiologic findings were previously described. We present a patient with a non-enhancing, solid cerebellar PA. Awareness of rare PA appearances is important for diagnosis and operative planning. Abstract: Pilocytic astrocytomas (PA) are slow-growing low-grade gliomas, commonly diagnosed as cerebellar tumors among the pediatric and adolescent population. Characteristic neuroradiologic findings in PA include a cystic mass with enhancing solid nodule. While uncommon radiologic features of PA, including non-enhancing cystic tumors, have been previously described, we present a unique case of a patient with a non-enhancing solid cerebellar PA. The main clinical, radiologic, and pathologic findings are discussed and the relevant literature reviewed. To our knowledge, this is the first reported patient with these radiologic features of PA, highlighting the need for awareness of uncommon presentations when discussing differential diagnosis and pre-operative planning for cerebellar tumors in the relevant age group.